(3eSFdI aj Md ETcGd ef bhGYO GdYdGeIs - (3eMeO Hf MSjf GdMGQKj GdgeOGfj GdYGedj, HgGA GdOjf , J (B1031 (3g` s
(3ChdgG (B:s
(3jbhd GdabjQ Edi Gddg GdZfi HgGA GdOjf eMeO GdYGedi eQJjf JhSW HjfgG GdeZQH s
(3BNQgG (B:s
(3hdG jLhR dg GdJYjjf dYOe HQGAI ReJg JeJ s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B102s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs